2022
DOI: 10.3233/jifs-213414
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED: Grid based blockchain framework for information management in surgical process proceedings

Abstract: Numerous academic and industrial research studies have focused on the feasibility of implementing blockchain-based healthcare systems data management that can transform the way data systems functioning, usage, and development can be effective. In this manuscript, the focus is on the development of a Grid-based blockchain structure formanaging the surgical process-related information in integrated systems. Considering the implications, scope of human error in the surgical processes, and the quantum of records i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…However, current models are designed for a specific objective. • The performance of the scheme needs to be examined for various quantum attacks Abdu 42 ✓ ✓ ✗ Grid-based blockchain • Optimizes the transaction query processing of surgical process records…”
Section: Insurance Organizationsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, current models are designed for a specific objective. • The performance of the scheme needs to be examined for various quantum attacks Abdu 42 ✓ ✓ ✗ Grid-based blockchain • Optimizes the transaction query processing of surgical process records…”
Section: Insurance Organizationsmentioning
confidence: 99%
“…Karunarathne et al examine the various security and privacy of IoT in the healthcare paradigm and suggested the security and privacy perspective solutions. Abdu et al 42 proposed a grid based blockchain to manage the surgical process related data. The surgical records requires the robust record storage by integrating quantum of records.…”
Section: State Of the Artmentioning
confidence: 99%